A portrait of germline pathogenic variants in high and moderate penetrance breast cancer genes in Brazil - Oliveira, Leandro Jonata de Carvalho; Rodrigues, Amanda Muniz; Fernandes, Carolina de Bustamante; Ramos do Rego, Fernanda Orpinelli; Koyama, Fernanda Christtanini; Souto, Andreza Karine de Barros Almeida; Santana, Thaiana Aragão; Gonzaga de Faria, João Paulo; Lima Bulcão, Marcela; Nascimento, Ivana Lucia de Oliveira; Silva, Ana Carolina Branco Neves; Gonçalves, Isabela Pessoa Elias; et al. (Frontiers in Oncology, 2024)
IntroductionThe prevalence of germline pathogenic/likely pathogenic variants (P/LP) in high and moderate penetrance (HMP) genes is approximately 7%–10% among breast cancer (BC) patients. The prevalence and spectrum of BC P/LP variants are affected by several factors. There are limited genetic data from Brazilian patients with BC.MethodsThis is a retrospective cross-sectional study that aims to evaluate the germline profile of P/LP variants in 13 HMP BC genes (BRCA1, BRCA2, PALB2, TP53, CDH1, NF1, PTEN, STK11, CHEK2, ATM, BARD1, RAD51C, and RAD51D) in patients diagnosed with BC in Brazil. All patients were tested using multigene NGS panels covering from 35 to 105 genes. Primary endpoint was the prevalence of P/LP variants in BRCA1/2 and in other HMP genes. Secondary endpoints were stratified analyses according to age and BC subtype.ResultsThis cohort involved 2,208 patients with BC from 2019 to 2023. Most patients (79.7%) were from Southeastern Brazil. The median age at genetic testing was 47 years, and most patients (59.4%) were ≤50 years. The BC subtype was available in 641 cases: 264 patients (41.2%) were HR+/HER2−, 116 (18.1%) were HER2+, and 261 (40.7%) had triple-negative breast cancer (TNBC). Overall, 215 (9.7%) had a P/LP in HMP genes, including 5.8% in BRCA1/2. The most frequent variants were found in BRCA2, BRCA1, and TP53. The founder variant R337H accounted for 79% of all TP53 pathogenic variants, representing 1% of the overall population. Deleterious variants in BRCA1/2 were more common in patients ≤50 years (7.7%) and TNBC (10.7%). In other HMP BC genes, the prevalence of P/LP variants did not significantly vary according to age and BC molecular subtype. The overall VUS rate in HMP genes was 19.6%.ConclusionIn Brazil, the epidemiology of deleterious variants in HMP is comparable to published US and EU cohorts. The Brazilian TP53 R337H is a prevalent variant in BC patients. Deleterious BRCA1/2 variants vary according to age and BC subtype. Our study gives a broader understanding of BC risk genes and has opened doors to optimized testing and surveillance strategies in Brazil.